2004
DOI: 10.1177/070674370404900205
|View full text |Cite
|
Sign up to set email alerts
|

The 5-Factor Model of Personality and Antidepressant Medication Compliance

Abstract: These results suggest that correlates of personality are important, although frequently ignored, predictors of compliance with antidepressant medication. Identifying predictors of medication compliance may help in the development of individualized treatment regimens and lead to improved therapeutic outcome in the treatment of MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
5
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 43 publications
3
52
5
1
Order By: Relevance
“…These results support the findings of Allan and Hodgson,14 who determined the best cooperators during orthodontic treatment were trustworthy. These results also coincide with the findings of Cohen et al, 9 who noted that patients high in modesty, another trait found within the agreeableness dimension of the modified BFI-10, displayed a positive correlation with patient adherence. Furthermore, they proposed that individuals scoring high in the agreeableness dimension may demonstrate more reverence to individuals of authority and be more likely to follow recommended medical instructions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results support the findings of Allan and Hodgson,14 who determined the best cooperators during orthodontic treatment were trustworthy. These results also coincide with the findings of Cohen et al, 9 who noted that patients high in modesty, another trait found within the agreeableness dimension of the modified BFI-10, displayed a positive correlation with patient adherence. Furthermore, they proposed that individuals scoring high in the agreeableness dimension may demonstrate more reverence to individuals of authority and be more likely to follow recommended medical instructions.…”
Section: Discussionsupporting
confidence: 91%
“…They did note that the agreeableness dimension demonstrated slightly reduced performance in the abbreviated model and recommended the addition of a third question, ''Is considerate and kind to almost everyone,'' to improve its performance, thus generating the modified BFI-10 instrument. This 11-item instrument would be a useful personality trait assessment tool for orthodontists because it (1) is succinct in nature, 4 (2) has been previously validated, 4 (3) is applicable in preadolescent populations, 7 and (4) has been used in the medical [7][8][9][10] and dental 8,11,12 literature. Few studies have investigated the relationship between a patient's personality characteristics and his potential adherence to certain treatment in orthodontics.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] Higher levels of Conscientiousness have been consistently associated with better adherence to chronic illness therapies. [25][26][27][28][29][30][31] Similar associations might exist between Conscientiousness and incomplete trial data, but no studies have addressed this question, and associations between other FFM factors and missing data are also unexplored.…”
Section: Per S Ona L I T Y a S Pr Edic Tor O F Mis Sing Datamentioning
confidence: 99%
“…[20][21][22][23][24] Higher levels of Conscientiousness have been consistently associated with better adherence to chronic illness therapies. [25][26][27][28][29][30][31] Similar associations might exist between Conscientiousness and incomplete trial data, but no studies have addressed this question, and associations between other FFM factors and missing data are also unexplored.We examined the relationship of FFM personality factors to missing data in a RCT of Homing in on Health (HIOH), which was developed to make the Chronic Disease Self-Management Program (CDSMP) 32,33 available to persons less able or willing to participate in group training. The goals were to determine whether in-home and telephone-delivered HIOH would enhance self-effi cacy, or confi dence for executing self-management tasks, and improve outcomes in persons with chronic conditions.…”
mentioning
confidence: 99%
“…En cuanto al tratamiento del dolor, la personalidad influye en el cumplimiento de las prescripciones terapéuticas en general y farmacológicas en particular, independientemente de la intensidad de los efectos secundarios y del grado de alianza terapéutica (62). Además, también puede determinar la eficacia de una intervención terapéutica.…”
Section: Influencia De La Personalidad En El Tratamiento Del Dolorunclassified